Посматрање ефеката интраозног приступа на упалне посреднике, функцију хематопоетских ћелија и коагулацијско-метаболичке поремећаје код хитних трауматичних хеморагичних шокова: Intraoseozni pristup kod urgentnog traumatskog hemoragijskog šoka - Deng, Gaorong; Jiang, Lang; Miao, Xin; Dong, Yuying; Gao, Xiang; Li, Zongfang (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to evaluate the impact of intraosseous (IO) access on inflammatory mediators, hematopoietic cell function, and coagulation-metabolic disturbances in patients presenting with emergency traumatic hemorrhagic shock (THS), thereby providing clinical evidence to refine IO resuscitation protocols in emergency settings.Methods: We conducted a randomized controlled trial involving 84 THS patients admitted between February 2024 and February 2025. Participants were allocated equally into two groups: the IO group (n=42), where vascular access was established via humeral or proximal tibial puncture, and the intravenous (IV) group (n=42), where conventional peripheral or central venous access was prioritized. Serial measurements were performed at baseline (T0), 24 hours (T1), and 72 hours (T2) post-intervention to assess: (1) inflammatory mediators (IL-1β, IL-6, IL-10, HMGB1, MDA); (2) hematopoietic parameters (CD34+ cell proportion, CFU-GM/BFU-E colony formation, CXCL12, EPO, and TPO); (3) coagulation profiles (PT, APTT, and D-dimer); and (4) tissue perfusion indicators (blood lactate and lactate clearance rate). Comparative analyses were conducted both between groups and across different time points.Results: The IO group demonstrated significantly elevated levels of IL-1β, HMGB1, and MDA at T1 and T2 compared to the IV group (P